The effect of melatonin on renal damage after crush injury in rats - Özel, Ş. Kerem; Köseo?ullari, A. Aysel; Kazez, Ahmet; Akpolat, Nusret; Ilhan, Nevin (My University, 2006)
Aim: Renal damage due to crush injury after earthquakes, remain a major cause of morbidity and mortality. The aim of this study was to investigate the effect of melatonin on renal damage in an experimental crush injury model. Material and Method: Twenty-four female Wistar-albino rats were divided into four groups. Group 1 was taken as control. In Group 2, 18 kg/cm2 of compression for two hours with a tissue compressor was applied to the left leg of the rats under general anesthesia, in Group 4, 20 mg/kg melatonin with its carrier was injected intraperitoneally, 5 minutes before and 12 hours after removal of the compressor. In Group 3, only the carrier was injected at the given periods. In all groups, serum samples for determination of myoglobin, urea, creatinine, potassium, creatinine phosphokinase and transaminases and bilateral nephrectomy materials for light microscopy, myoglobin immunehistochemical staining, tissue nitric oxide and malondialdehyde determination were taken 24 hours after the first procedures. Results were statistially evaluated. Results: Serum transaminase levels were found to be increased and tissue nitric oxide was found to be decreased in rats with crush injury (p<0.05). Comparisons of other biochemical parameters were not significant. In light microscopy, hydropic degeneration in the proximal tubules was found in crush group when compared to control (p=0.005). This damage was reversible with melatonin (p=0.024). Immunohistochemically, there was a significant increase in myoglobin in the vessels, proximal tubules and glomerules of the kidneys of crush group when compared to control and a significant decrease after melatonin in comparison with crush group (p<0.05). Conclusion: In conclusion, crush injury causes degeneration in the proximal tubules of the kidney. Myoglobin released after muscle breakdown is thought to be responsible from this effect. Melatonin, as an antioxidant, prevents renal damage generated with this mechanism. Early antioxidant therapy for crush injury may be used in the future to prevent renal damage.
Ezilme yaralanmasi oluşturulan siçanlardaki böbrek hasarina melatoninin etkisi
Keywords: Crush injury; Kidney; Melatonin